Exploring the experience of informal caregivers of dependent elderly people with the well-being valuation method - Lyu, Tongzhou; Yuan, Suwei; Xu, Yanping; Liu, Wenwei (Frontiers in Psychiatry, 2025)
IntroductionAlthough informal caregivers are the primary providers of long-term care for the elderly globally, research on the impact of caregiving experiences on the well-being of caregivers is relatively limited.MethodsThis study conducted interviews with 297 family informal caregivers in Shanghai, measured their subjective burdens, and applied the well-being valuation method to calculate the monetary value of the welfare changes resulting from caregiving burdens.ResultsAccording to the findings, sub-dimensions of the Chinese version of the Caregiver Reaction Assessment (CRA) of disrupted schedule, lack of family support, and self-esteem were significantly related to caregivers’ well-being. For caregivers with average income and average CRA scores, the impact of caregiving experiences on their well-being level was equivalent to a monthly income reduction of 226.69 RMB (4.7% of their monthly income).DiscussionThis paper provides a new and useful perspective for the evaluation of long-term care policies, and suggests prioritizing the alleviation of caregivers’ schedule and social relationship burdens, and understanding the ‘intrinsic coping mechanisms’ of caregiving responses from an economic perspective.